Hukum Trust dalam Sistem Hukum Common Law dan Civil Law - Ruth Felyta Worang (CV Rewang Rencang, 2025)
Trust law, which originated in England with its unique legal characteristic inherent to the common law system, has, under influence of globaligzation, been adopted and applied in civil law jurisdiction. One of its defining features, dual ownership, poses significant challenges when implementing trust law in countries with civil law systems. However, research indicates that civil law jurisdiction such as India, Japan, and Indonesia have adopted the trust concept by incorporating domestic legal principles, such as the principles of obligation, contractual frameworks, and the application of the jus-in-personam theory, to address the fundamental differences with the dual ownership principle. These adaptations, tailored to the respective legal systems of civil law countries, have enabled the application of trust law without relying on the dual ownership principle.